Simulation Study on the Evolution Behaviour of Endogenous Third Bodies in the Rough Friction Interface During Braking and Their Impact - Lu Jin; Shengfang Zhang; Guotao Ru; Jian Yin; Li Shi; Xin Li; Zhihua Sha; Yu Liu (Machines)
During braking, high-power wind turbine disc brake friction pairs experience thermo-mechanical interactions at the interface, which lead to both physical and chemical changes. The friction interface features asperities and embedded hard particles within the substrate. Wear debris from these asperities or dislodged hard particles accumulates at the interface, continuing to participate in the friction process—a phenomenon known as the “endogenous third body”. Throughout braking, the microscopic morphology and contact conditions of the interface evolve dynamically. The stress–strain distribution and vibration behaviour of the friction system, influenced by the endogenous third body, also vary with braking parameters. This study employs the W-M fractal theory to develop a finite element model of a rough friction interface containing hard-particle endogenous third bodies. The model is validated through experimental testing. Based on the performance test parameters of high-power wind turbine disc brakes, a simulation is conducted to analyse the contact friction process involving the endogenous third body at the rough interface between the brake disc and brake pad. The simulation reproduces the formation process of the endogenous third body and reveals its evolutionary stages, including “ploughing”, “gap-filling”, and “aggregation”. Additionally, the study examines changes in the internal stress–strain and vibration states of the friction system under varying braking speeds (5 m/s to 35 m/s) and braking loads (3 MPa to 6 MPa). The findings demonstrate how different braking parameters influence the friction system containing the endogenous third body. The results showed that when the braking speeds were 5 m/s, 15 m/s, 25 m/s, and 35 m/s, and the braking load was 6 MPa, the average amplitude of the brake pads was the smallest, at 0.017 mm, 0.021 mm, 0.025 mm, and 0.020 mm, respectively. This research provides valuable insights into the three-body contact friction mechanism at the micro-braking interface, the formation of composite material third bodies, and the role of wear-stage third bodies in affecting the friction interface.